Mobile-Assisted Language Learning (MALL) and English Language Proficiency among University EFL Students: A Quantitative Analysis - Siti Aminah Hasibuan; Assajidah (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2026)
Mobile-Assisted Language Learning (MALL) has gained increasing attention in higher education as a means of enhancing English as a Foreign Language (EFL) learning through the integration of digital technologies. This study aims to investigate the relationship between the use of Mobile-Assisted Language Learning (MALL) and English language proficiency among university EFL students using a quantitative research approach. A total of 120 undergraduate students from a public university participated in the study. Data were collected through a MALL usage questionnaire and a standardized English proficiency test covering listening, speaking, reading, and writing skills. The questionnaire was designed to measure students’ frequency of mobile device use, types of mobile applications employed, and perceived usefulness of MALL in English language learning. The collected data were analyzed using descriptive statistics and inferential statistical techniques, including correlation and multiple regression analyses. The results revealed a significant positive relationship between MALL usage and students’ overall English language proficiency. Specifically, higher levels of engagement with mobile learning applications were associated with improved performance in vocabulary acquisition, reading comprehension, and listening skills. The regression analysis further indicated that the frequency of MALL use and students perceived usefulness of mobile learning significantly predicted English language proficiency, accounting for a substantial proportion of the variance. The findings suggest that MALL can serve as an effective supplementary tool in university EFL classrooms by promoting flexible, learner-centered, and autonomous learning experiences. This study provides empirical evidence supporting the integration of mobile technologies into English language instruction at the tertiary level. Pedagogical implications include the need for instructors to strategically incorporate mobile-based activities and guide students in selecting appropriate applications to maximize learning outcomes. Future research is recommended to explore experimental designs and longitudinal studies to further examine the causal effects of MALL on specific language skills.